Search for anomalous Wtb couplings in single top quark production in p(p)over-bar collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Aoki, M.; Askew, A.; et al. (Elsevier B.V., 2012)
We present new direct constraints on a general Wtb interaction using data corresponding to an integrated luminosity of 5.4 fb(-1) collected by the do detector at the Tevatron p (p) over bar collider. The standard model provides a purely left-handed vector coupling at the Wtb vertex, while the most general, lowest dimension Lagrangian allows right-handed vector and left- or right-handed tensor couplings as well. We obtain precise limits on these anomalous couplings by comparing the data to the expectations from different assumptions on the Wtb coupling. Published by Elsevier B.V.